Decreased prevalence of Moraxella catarrhalis in addition to Streptococcus pneumoniae in children with upper respiratory tract infection after introduction of conjugated pneumococcal vaccine: a retrospective cohort study. (April 2021) - Littorin, N.; Rünow, E.; Ahl, J.; Resman, F.; Riesbeck, K.
Abstract: Objectives: To study effects of the introduction of pneumococcal conjugate vaccines (PCV) on the interspecies dynamics of Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis in preschool children with respiratory tract infection. Methods: Nasopharyngeal samples from children aged ≤6 years with upper respiratory tract infection ( n = 14 473) in South Sweden were analysed during 14 consecutive years, 5 years before and 9 years after PCV introduction. The yearly prevalence was calculated, and multivariate count regressions between prevalence and estimated yearly proportions of vaccinated children were performed. Associations between pneumococcal serotypes and the other pathogens were assessed. Results: When comparing the prevaccine period with the years after introduction, the prevalence of S. pneumoniae decreased by 65.2% (16.4 to 5.7 per 1000 individuals; p < 0.001), whereas M. catarrhalis and H. influenzae decreased by 52.1% (21.5 to 10.3 per 1000 individuals; p < 0.001) and 46.6% (13.6 to 7.3 per 1000 individuals; p < 0.001), respectively. In multivariate negative binomial regressions adjusted for yearly numbers of samples taken, S. pneumoniae and M. catarrhalis were significantly negatively associated with increasing vaccine coverage proportions (adjusted prevalence ratio (aPR) = 0.17; p < 0.001 and aPR = 0.48; p < 0.001, respectively), whereas H. influenzae (aPR = 0.75; p = 0.17) was not. In addition, the proportion of cultures positive for S. pneumoniae as well as M. catarrhalis was significantly lower in the postvaccine period compared to the prevaccine period, while this was not the case for H. influenzae. A significant positive association between certain PCV serotypes and simultaneous growth with M. catarrhalis was observed. Conclusions: After introduction of PCV, the prevalence of M. catarrhalis in addition to S. pneumoniae in children with respiratory tract infection decreased; this was also the case after adjusting for reduced numbers of samples taken. This may partly be attributed to a positive association between PCV serotypes and M. catarrhalis.